2021
DOI: 10.3389/fpsyg.2021.610002
|View full text |Cite
|
Sign up to set email alerts
|

6-Month-Old Infants’ Sensitivity to Contingency in a Variant of the Mobile Paradigm With Proximal Stimulation Studied at Fine Temporal Resolution in the Laboratory

Abstract: Infants’ ability to monitor “sensorimotor contingencies,” i.e., the sensory effects of their own actions, is an important mechanism underlying learning. One method that has been used to investigate this is the “mobile paradigm,” in which a mobile above an infant’s crib is activated by motion of one of the infant’s limbs. Although successfully used in numerous experiments performed in infants’ homes to investigate memory and other types of learning, the paradigm seems less robust for demonstrating sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We believe that developing new methodological protocols without using learning criteria is particularly essential to evaluating whether memory findings reflect the true state of the world. In recent years, some studies developed alternative operational definitions of learning such as a movement burst at the beginning of the extinction phase (Zaadnoordijk et al, 2018(Zaadnoordijk et al, , 2020 and response differentiation between the limbs (Popescu et al, 2021). These studies, without using particular selection criteria, demonstrated that young infants can learn sensorimotor contingencies.…”
Section: Methodological Integritymentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that developing new methodological protocols without using learning criteria is particularly essential to evaluating whether memory findings reflect the true state of the world. In recent years, some studies developed alternative operational definitions of learning such as a movement burst at the beginning of the extinction phase (Zaadnoordijk et al, 2018(Zaadnoordijk et al, , 2020 and response differentiation between the limbs (Popescu et al, 2021). These studies, without using particular selection criteria, demonstrated that young infants can learn sensorimotor contingencies.…”
Section: Methodological Integritymentioning
confidence: 99%
“…This created a unique way of measuring memory in the mobile paradigm that is different from the other paradigms measuring memory (e.g., deferred imitation, Meltzoff, 1985; preferential looking, Robinson & Pascalis, 2004; habituation, Fantz, 1965). Nevertheless, it is also important to note that newer versions of the mobile paradigm used alternative methodological approaches (e.g., alternative operational definitions of learning, Popescu et al, 2021; Zaadnoordijk et al, 2018, 2020). This unique methodological approach of the traditional methodological protocol makes it interesting to examine how these methodological choices affect the reliability of the results.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation